Família do doente com câncer: percepção de apoio social - Rodrigues, Juliana Stoppa Menezes (Universidade Federal de São Carlos, 2012)
Cancer is a chronic degenerative disease, considered a public health problem and one of the consequences is to induce the family to live a long time with a diseased family member. This can brake the family apart, because of the treatment process and also causing a demand for a social network that offers the support needed to cope with this complex trajectory. This study is quantitative, descriptive, exploratory cross-sectional, which aimed to characterize the feeling from the families about the social support in cancer patients, assisted by a specialized service in a city of Sao Paulo. All researches considerations with humans were respected. Interviews were conducted with every family that met the inclusion criteria, comprising 69 families and 161 people total. It was used for data collection the following instruments: The family profile of the patient with cancer , Social Support Scale of the Medical Outcomes Study (MOS-SSS) and The Convoy of Social Support Diagram. The interviews were done at their homes with at least family dyads and also after the consent and respecting the date/time stipulated by the family. Data were coded and entered in Microsoft Excel and Biostat 5.0 and analyzed using descriptive and correlational statistics. Patient profiles showed: 65% were female, aged 28-89 years-old and the most prevalent neoplasm was breast cancer (36%), of which 48% were in advanced stages of disease. The second most frequent cancer was prostatic (10%), of which 72% were older 65 years-old. The Convoy of Social Support Diagram showed 506 members in the patient social networks, between 1-89 years-old. The most social network members was female, who knew the patient for 33 years-old on average and 78.7% lived less than 30 minutes from the patient house. The profiles of families showed 28% with only two people in their composition, living in social class D (70%). The MOS-SSS identified that affective support was the most frequently mentioned (88), followed by emotional support (81), material support (80), information support (78) and positive social interaction (76). An average positive correlation was found (p=0.002 e r=0.4) between social support and number of people on the network. Statistically significant associations were found with p<0.0001 between the dimensions of social support and p<0.0003 between the variables number of women in social networks and social support, indicating that social support tends to be greater in larger social network and especially if people are female. It is considered that the possibilities for support of the family are diverse and health professionals have an important role in increasing the viability of the contacts between the micro system (family) and supra system (neighborhood, community and religious organizations), but they must be open to the family, realizing it like a unit of care, recognizing the social network as a fundamental source in the maintenance of wellbeing which improves life satisfaction and effective support. So, identifying and giving the social network its value in the family context and understanding the real needs and potential of the family unit, helps the health professional in the planning of the care centered in the family. This may improve the confront of the families face difficulties inherent to chronic situation and provides a humanized care. The implement of public policies which promote access of population to social support networks is very important.
Keywords: Enfermagem; Família; Neoplasias; Apoio social; Social Support; Social Network; Neoplasms; Family; Nursing; CIENCIAS DA SAUDE::ENFERMAGEM